CATHARSIS AND THE INDIAN MIND: UNDERSTANDING INTROVERSION IN PSYCHOSOMATIC HEALING - Kalda, Prapti; Kundu, Tapas; Kundu, Rita (International Journal of Research -GRANTHAALAYAH, 2025)
Catharsis, the act of releasing deep, pent-up emotions, plays a powerful role in both psychology and homoeopathy. It serves as a bridge between mind and body, helping hidden feelings rise to the surface so that they can be expressed, understood, and eventually dissolved. This emotional release restores inner balance and strengthens the body’s vital force, paving the way for true healing. This article sheds light on how emotional suppression and introversion shape the health of individuals in Indian society. Traditionally, Indian culture values emotional restraint and collective harmony. While this fosters social stability, it also encourages people to keep their emotions bottled up. Over time, this inward tendency can contribute to a range of psychosomatic disorders, illnesses that reflect the impact of the mind on the body, including digestive problems, skin conditions, anxiety, and hypertension. This researches work highlights how catharsis can be a crucial step in recovery. By allowing people to express repressed feelings in a safe, conscious way, emotional energy is released and healing can begin. Homoeopathy naturally supports this process, as it considers the emotional and mental state an integral part of treatment. Remedies suited to introverted constitutions help patients open up, facilitating both emotional release and physical improvement. Through clinical insights, cultural understanding, and homoeopathic principles, this article explains why catharsis is not just a concept but a practical tool for healing psychosomatic diseases. It encourages practitioners to create spaces where patients feel safe to express their inner worlds, because when emotions find their voice, the body often finds its relief.